EXPLORING SERUIT AND IT'S TRANSFORMATION, THE HERITAGE CULINARY FROM LAMPUNG INDONESIA - Sandi Aderama Handika; Pipin Kusumawati; Moch. Nur Syamsu (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2026)
Seruit is a traditional cuisine from Lampung, with a blend of Indonesian sambal (chili paste), fish, and various vegetables. In addition to fulfilling dietary requirements, Seruit symbolizes the philosophy, culture, and social values preserved by the Lampung community. The impact of modernization has caused the younger generation to favor trendy and convenient foods for its practicality. To maintain continuous acceptability from diverse groups, adaptive strategies were required in the development of Seruit that maintain its philosophical principles. This research aims to identify the uniqueness of Seruit and its transformations in response to modern demands, ensuring its sustainability and establishing it as a cultural and culinary icon of Lampung Province. This research employed a qualitative methodology with an ethnographic approach. Data were collected through in-depth interviews, participant observation, and documentary review. Research revealed that the uniqueness of Seruit were attributed to its local ingredients, mixing process of Seruit's ingredients (pijok-pijok), and Seruit's serving and eating styles (nyeruit). Seruit has experienced four transformations to date: preservation techniques, serving styles, sambal variants and ingredients, and consumption space. These transformations expand Seruit's presence in public and commercial areas, while strengthening its status as a cultural and culinary Seruit, Lampung, transformation, heritage, modernization.